HIV and AIDS Data Hub for Asia Pacific: a regional tool to support strategic information needs - Ye Yu Shwe; Amala Reddy; khin Cho Win Htin (World Health Organization Regional Office for the Western Pacific, 2012)
The 2011 global commitments towards controlling HIV made by Asia-Pacific countries require considerable improvement in strategic information and response tracking. The HIV and AIDS Data Hub can serve as an important tool for stakeholders with its regional database of subnational indicators, web site and data synthesis capacity.